2016
DOI: 10.1063/1.4940679
|View full text |Cite
|
Sign up to set email alerts
|

On the rogue wave propagation in ion pair superthermal plasma

Abstract: Effects of superthermal electron on the features of nonlinear acoustic waves in unmagnetized collisionless ion pair plasma with superthermal electrons have been examined. The system equations are reduced in the form of the nonlinear Schrodinger equation. The rogue wave characteristics dependences on the ionic density ratio (ν = n–0/n+0), ionic mass ratio (Q = m+/m−), and superthermality index (κ) are investigated. It is worth mentioning that the results present in this work could be applicable in the Earth's i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
61
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 35 publications
5
61
0
Order By: Relevance
“…Recently, a bounce of authors has been used NLS equation to understand different nonlinear phenomena (MI and rogue waves), which are observed in laboratory and space plasmas. Abdelwahed et al [25] examined rogue waves characteristics are totally depended on the ionic density ratio, ionic mass ratio, and superthermal parameter in ion pair superthermal plasma. Gill et al [5] studied MI of dust acoustic solitons in multicomponent plasma with kappa distributed electron and ions, where they observed presence of positive dust component modify the domain of the MI and localized envelope excitations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a bounce of authors has been used NLS equation to understand different nonlinear phenomena (MI and rogue waves), which are observed in laboratory and space plasmas. Abdelwahed et al [25] examined rogue waves characteristics are totally depended on the ionic density ratio, ionic mass ratio, and superthermal parameter in ion pair superthermal plasma. Gill et al [5] studied MI of dust acoustic solitons in multicomponent plasma with kappa distributed electron and ions, where they observed presence of positive dust component modify the domain of the MI and localized envelope excitations.…”
Section: Introductionmentioning
confidence: 99%
“…The field of MI and RWs has been considered one of the highly interdisciplinary areas of research involving plasma physics, [12] oceanography, [28] Bose-Einstein condensation, [29] optics, [30] superfluid helium, [31] and even finance [32] A number of authors have theoretically studied different criteria of MI and RWs in many PIPM [3,12,33] and confirmed them in laboratory experiments. The nonlinear Schrödinger equation (NLSE) admits interesting rational solutions named rogue waves (RWs), also known as freak waves, extreme waves, and killer waves, in the MI region.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have devoted their attention to solve the mystery of these colossal waves because of their intrinsically arbitrary nature and their complex formation mechanisms. Abdelwahed et al [33] studied IA rogue waves (IARWs) in PIPM in the presence of super-thermal electrons. [34][35][36] Bailung et al [34] have observed peregrine solitons in a multi-component plasma with negative ions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results were shown to be important in the D-and F-regions of the Earth's ionosphere. In an another work, Abdelwahed et al [27] investigated the propagation of rogue waves in superthermal plasmas with a pair of ions. Different characteristics of the rogue waves so generated have been studied by the effects of the number densities as well as the superthermality of ions.…”
mentioning
confidence: 99%